Inversionless amplification of coherent terahertz radiation - Janke, Christof; Haring Bolivar, Peter; Bartels, Albrecht; Kurz, Heinrich; Künzel, Harald (My University, 2003)
We experimentally demonstrate inversionless amplification of the emission from electronic transitions in a solid state system inside a cavity. A semiconductor-based terahertz (THz) emitter is exposed to a coherent, phasematched THz background field during the emission process leading to an increase in the overall emitted THz power of more than one order of magnitude . The experimental concept and results are discussed within a three-level model and an extended density matrix approach.
Keywords: 530